SAHAM GOTO MENYENTUH AUTO REJECT BAWAH (ARB), SAATNYA SELL ATAU BUY - Try Wulandari (Jurnal Ecoment Global, 2023)
GOTO shares have always fallen since the initial IPO was carried out with various factors. As an investor, you need to do an analysis before making an investment decision. There are many analysis tools that can be used such as fundamental analysis and technical analysis. For GOTO stock, the fundamental analysis is quite good, while the technical analysis is not good because the stock price continues to fall. As of January 2023, GOTO's share price is slowly increasing even though it is still low. Book prices have also not been touched so there is a possibility that they could go up, but this is still in the form of assumptions and predictions. The results of this study are expected to be a reference before making investment decisions. However, the investment decision is entirely owned by the investor.